Influence of technology, student's attitude and reading strategies toward reading habit: an investigation among the Bachelor of Science in Information Studies (hons) (Library and Information Management) (IM220) students in UiTM Kedah/ Rosfadilah Mohd Nawi - Mohd Nawi, Rosfadilah (Faculty of Information Management, 2011)
The title of this research was “Influence of technology, student’s attitude and reading strategies toward reading habit: An investigation among the Bachelor of Science in Information Studies (Hons) (Library and Information Management) (IM220) students in UiTM Kedah”. The respondents of this research focused on IM220 students in UiTM Kedah. Problem statement indicated that it is a trend that students do not reading for pleasure instead of finishing assignment and during examination. Aten Long (1984) distinguished that the reading interest and habit of Malaysians is very low. Libraries are not fully utilized. There are three independent variables used in this research consist of technology, attitude and reading strategies. The instrument used in this research was questionnaire to collect data and use quantitative method. Moreover, Statistical Package for Social Science (SPSS) is used to analyse data.